Sensitivity of atypical lateral fire spread to wind and slope. Issue 4 (22nd February 2016) - Simpson, Colin. C.; Sharples, Jason J.; Evans, Jason P.
Abstract: This study presents new knowledge of the environmental sensitivity of a dynamic mode of atypical wildland fire spread on steep lee‐facing slopes. This is achieved through a series of idealized numerical simulations performed with the Weather Research and Forecasting (WRF) and WRF‐Fire coupled atmosphere‐fire models. The sensitivity of the atypical lateral fire spread across lee slopes is tested for a varying background wind speed, wind direction relative to the terrain aspect, and lee slope steepness. The results indicate that the lateral spread characteristics are highly sensitive to each of these environmental conditions, and there is a broad agreement with the empirical thresholds calculated for lateral spread events observed in the 2003 Canberra bushfires. A theory to explain these environmental thresholds and their apparent interdependency is presented. The results are expected to have important implications for the management of wildland fires in rugged terrain. Key Points: Lateral fire spread on lee slopes is sensitive to the background wind and lee slope steepness Ambient and fire‐induced vorticity associated with the atypical lateral fire spread Environmental thresholds are apparent in wind and slope for dynamic fire spread